If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 17 + -4x = 9 + 4x + -7 Reorder the terms: 17 + 5x + -4x = 9 + 4x + -7 Combine like terms: 5x + -4x = 1x 17 + 1x = 9 + 4x + -7 Reorder the terms: 17 + 1x = 9 + -7 + 4x Combine like terms: 9 + -7 = 2 17 + 1x = 2 + 4x Solving 17 + 1x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 17 + 1x + -4x = 2 + 4x + -4x Combine like terms: 1x + -4x = -3x 17 + -3x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 17 + -3x = 2 + 0 17 + -3x = 2 Add '-17' to each side of the equation. 17 + -17 + -3x = 2 + -17 Combine like terms: 17 + -17 = 0 0 + -3x = 2 + -17 -3x = 2 + -17 Combine like terms: 2 + -17 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| x+7m=78m^2 | | 346*65=x | | 4x+7x-3x=34+6 | | -10x+(-5)-x=28 | | -10x+5-x=28 | | 34*15=x | | -3y-3=1+2y | | -9x-4=203 | | X^2+94=-2 | | 3px(-4)=6 | | 5y-4=19y+108 | | 3x-12+8x=87 | | 0=3x(x-4)(x-1) | | -x+x+30= | | 0=3x(x-4)(x-1) | | 2x-48=52 | | 2x-48=52 | | x+Bx+25=(x+5) | | 2a+3b-5a= | | 6x-4=44-2x | | 2(x-6)-9=19-6x | | 10+.3x=x-2 | | 48-2x=8x+8 | | 10+1.3x=x-2 | | 42975-125m=45000-350m | | 0.3t+-0.3t=x | | 5(2-4t)+3t=5t+7 | | 0.37(28+62.7x)=56.758 | | 11+m=9 | | 5.6x^2+40x+400=0 | | 9007-5667=x | | -2y-1(3y-9)=7+9(-3-y) |